Diversidad de la vegetación durante su recuperación tras una creciente extraordinaria del Río Paraná Medio (Argentina) - A. Franceschi, Eduardo (2010)
River floodplains have a high biological diversity that is intensely influenced by vegetation dynamics, changes in space and time scales, and the river`s hydrological regime. The vegetation composition of the medium and lower Paraná River has been analyzed previously, with different approaches and criteria that cannot be compared. The aim of this study is to analyze the diversity of the herbaceous vegetation over long time spans, from its regeneration after a catastrophic flood to its recovery, in the North and South sites of the flooding valley of the Medium Paraná River. The first sampling of a pioneer community was performed after the 1982-83 catastrophic flood, and included the surveillance of two plots in two successive recovery stages. Floristic com-position and cover-abundance of all species were recorded per plot. Floristic richness, using jackknife, Shannon and Hurlbert diversity and Simpson dominance curves were calculated for each site and for each survey, using EcoSim (software). Floristic richness was higher in the North of Medium Paraná, while dominance was higher in the South. Diversity indexes did not varied significantly and resulted in relatively stable values, because its components compensate each other.